Toxicity of Thiamethoxam on Field-Collected Sand Flies (Diptera: Psychodidae) From Different Regions of Turkey. Issue 1 (10th September 2019) - Arserim, Suha K; Çetin, Hüseyin; Yetişmiş, Kardelen; Omondi, Zeph Nelson; Özbel, Yusuf
Abstract: Phlebotomine sand flies (Diptera: Psychodidae) are the vectors of human and canine leishmaniasis, sand fly fever, and other arboviruses and bacteria. The control of sand flies is recommended by World Health Organization throughout the world. In this study, we investigated the susceptibility of field-collected sand flies against thiamethoxam in Turkey. The adult sand flies collected were from five different locations in three provinces; Yeşilöz and Büyükpınar districts in Antalya province, Develi district in Kayseri province, and Üçpınar and Bayındırlık districts in Manisa province. They were investigated using two different doses (0.125 and 0.25 g ai/m 2 ) of thiamethoxam under laboratory conditions. After 1-h exposure, all sand flies were found highly susceptible to thiamethoxam and both test doses caused 100% mortality after 24 h. Considering the KDT50 time, flies collected from Yeşilöz district in Antalya province were found to be most sensitive and flies collected from Üçpınar district in Manisa province were found as the most resistance to thiamethoxam. The results show that Turkish sand flies were highly susceptible to thiamethoxam and it can be used for the control of sand flies in the field.